Employment of Persons with Disabilities as Competitive Advantage: An Analysis of the Competitive Implications - Boris Miethlich; Anett G. Oldenburg (33nd International Business Information Management Association Conference (IBIMA), Education Excellence and Innovation Management through Vision 2020, Granada, Spain, 10-11.04.2019, 2019)
People with disabilities (PWD) represent a largely untapped market and customer segment worldwide, as well as an enormous untapped workforce potential. Although there are indications in the literature that the employment of PWD can bring many advantages for companies, the effects on companies and the resulting competitive advantages have rarely been empirically investigated. This article aims to analyze the competitive implications of the employment of PWD, as part of the corporate social responsibility (CSR) strategy. The research is based on a literature review. The selected literature was evaluated regarding the competitive advantage using the value-rarityimitability-organisation (VRIO) framework. The results show that the employment of PWD is valuable, rare, and costly to imitate. If a company succeeds in using this resource effectively, this leads to a sustainable competitive advantage. An established corporate culture is a mandatory prerequisite to integrate PWD successfully. This prerequisite represents an imitation barrier. The promotion of the employment of PWD gives access to a new pool of applicants and can contribute to mitigating or preventing a future shortage of skilled workers. The employment of PWD does not wear off as a human resource. The concept can be transferred to different technologies, products, and markets. The sensitivity gained about people with disabilities can open new markets and customer segments. Therefore, PWD's employment as part of the value creation strategy can make a long-term contribution to the company's success and represent a sustainable competitive advantage.
Keywords: J14; M14; I18; 330; CSR; Persons with disabilities; Diversity; Employment; HRM